PENGALAMAN KLIEN CHRONIC KIDNEY DISEASE (CKD) MENJALANI HEMODIALISIS DI RUMAH SAKIT UMUM (RSU) HAJI SURABAYA - Caturia Sasti Sulistyana (STIKes Adi Husada, 2018)
ABSTRACT Chronic Kidney Disease (CKD) is one of serious health problems in main accesing morbidity and mortality in the world, and caused of which weakens illness. Clients who undergoing hemodialysis had been relying on an dialysis engine for life, which made their negative perception to their prognosis of the illness. The aim of this research to explore their experiences when undergoing hemodialysis as caused their anxiety. This research used explorative descriptive design with quality approach to explore, understand, explan of their comprehension, assumption, felt, source of informations, coping mechanism, sosial support about their illness. The results of this research were they had bad knowledge and negative perception of their illness and hemodialysis, and felt of shock, afraid, sad, despair, and denial when the first time diagnosed by doctor to undergoing hemodialysis. They were not acceptance on their conditions, which to made on opposed of the therapy and spirituality distress. They deems hemodialysis is so terrible and causes death. The conclusion of this research is negative perception occurs on CKD clients undergoing hemodialysis. The negative perception to made their felt so bad and axiety. The suggestion on the next research used critical review to develop a nursing intervention according the results. Keywords: Experience, CKD clients undergoing hemodialysis